Exploring work-family conflict among married Muslim women: A qualitative case study - Farhan Toha; Arthur Huwae (LP2M Universitas Sarjanawiyata Tamansiswa, 2025)
Work-family conflict (WFC) is a common phenomenon experienced by women who undergo dual roles as workers and family members. This study aims to explore the experiences and contributing factors of WFC among married Muslim women who undertake dual responsibilities in work and family domains. This research used a qualitative approach with a case study design. The participants in this study were ten Muslim women who were selected using a purposive sampling technique. Data were collected through semi-structured interviews and analyzed using Miles and Huberman's interactive analysis technique. The results showed that participants experienced difficulties dividing time between work and family, psychological pressure due to high work demands, and the influence of work stress on family interactions. Despite facing the challenges of WFC, participants showed adaptation strategies, such as effective time management, separation of roles between work and family, and utilization of technology to support work and family life balance. Support from spouses and family also played an essential role in helping participants navigate their dual roles. In addition, the motivation to keep working is not only based on economic aspects but also on fulfilling psychological and social needs. This study provides insight into the dynamics of WFC in Muslim women as well as strategies that can be used to overcome these challenges.